2020
DOI: 10.1186/s10020-020-00241-8
|View full text |Cite
|
Sign up to set email alerts
|

PTEN inhibitor improves vascular remodeling and cardiac function after myocardial infarction through PI3k/Akt/VEGF signaling pathway

Abstract: Background Myocardial infarction (MI) is the leading cause of death from cardiovascular disease (CVD). Currently, the efficacy for MI treatment remains unsatisfactory. Therefore, it is urgent to develop a novel therapeutic strategy. Methods Left anterior descending arteries (LAD) of mice were ligated to induce MI. Another set of mice were intravenously injected with PTEN inhibitor BPV (1 mg/kg) 1 h after LAD ligation and continued to receive BPV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 45 publications
1
18
0
1
Order By: Relevance
“… Liang et al (2020) have reported that cardiac-specific PTEN knockout can reduce the inflammatory response and fibrotic remodeling to protect the heart after MI injury. Several researches reported the increased expression of PTEN in MI ( Parajuli et al, 2012 ; Feng et al, 2020 ), which were consistent with our results. As PTEN was reported to play roles in cell apoptosis and survival through PI3K/AKT pathway ( Wu et al, 2006 ; Mocanu and Yellon, 2007 ), PTEN reducing became a potential therapeutic target for increasing myocardial survival ( Oudit et al, 2004 ; Liang et al, 2021b ).…”
Section: Discussionsupporting
confidence: 93%
“… Liang et al (2020) have reported that cardiac-specific PTEN knockout can reduce the inflammatory response and fibrotic remodeling to protect the heart after MI injury. Several researches reported the increased expression of PTEN in MI ( Parajuli et al, 2012 ; Feng et al, 2020 ), which were consistent with our results. As PTEN was reported to play roles in cell apoptosis and survival through PI3K/AKT pathway ( Wu et al, 2006 ; Mocanu and Yellon, 2007 ), PTEN reducing became a potential therapeutic target for increasing myocardial survival ( Oudit et al, 2004 ; Liang et al, 2021b ).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, stimulating angiogenesis ameliorates cardiac remodeling after myocardial infarction (Laan et al 2009 ). CD31 plays an important role in endothelial cell intercellular junctions and is widely used as a marker for angiogenesis quantification (Feng et al 2020 ; Ho et al 2012 ). We, therefore, assessed the de novo formation of microvessel in peri-infarct myocardium at 14 days post-MI through CD31 staining and expression.…”
Section: Resultsmentioning
confidence: 99%
“…PTEN has been extensively studied in tumor development and angiogenesis, but increasing evidence demonstrated that PTEN was also closely related to cardiovascular disease ( Parajuli et al, 2012 ). It was reported that the inhibition of PTEN cannot only reduce cardiomyocyte apoptosis, oxidative stress, and DNA damage in ischemic injury ( Gong et al, 2021 ) but also shrink infarction areas and improve cardiac function in MI mice ( Feng et al, 2020 ). We observed that the expression of PTEN in both protein and mRNA in H9c2 cells have risen sharply after H/R injury, but was restrained by SW-exo and miR-140-3p.…”
Section: Discussionmentioning
confidence: 99%